Complete chloroplast genome sequence of the medicinal plant ramie (Boehmeria nivea L. gaud) and its phylogenetic relationship to other Urticaceae species. Issue 3 (4th March 2021) - He, Xiangyu; Zheng, Zihong; Wang, Qirui; Zhou, Manjia; Liao, Guanghui; Ge, Yuqing; Cheng, Rubin
Abstract: Ramie ( Boehmeria nivea L. Gaud) is a traditional fiber crop and important medicinal plant belonging to the family Urticaceae. In this study, we determine the complete chloroplast genome sequence of B. nivea . The assembled chloroplast genome is 156065 bp in length and shares the conserved quadripartite structure as other cp genomes in Boehmeria . The genome contains 131 genes, including 84 protein genes, 8 rRNA genes, 37 tRNA genes and 2 pseudo genes. There are 17 duplicated genes in the IR region. The overall GC content of B. nivea is 36.33%, with the highest GC content of 42.72% in IR region. A total of 67 simple sequence repeats are identified in the cp genome of B. nivea . Phylogenetic analysis demonstrated that B. nivea clustered together with B. tomentosa, further forming a monophyletic group with the species of Debregeasia and Pipturus. This work provides basic genetic resources for developing robust markers and investigating the population genetics diversities for B. nivea.